Estrus Synchronization and Conception Rates Using Locally Prepared Methylacetoxy- progesterone Sponges in Cyclic and Acyclic Nili-Ravi Buffaloes (Bubalus bubalis) - R Kausar*, SA Khanum, M Hussain, T Hussain, N Ahmad1, L Ahmad2 and NA Qureshi2 (Pakistan Veterinary Journal, 2013)
A study was conducted to evaluate the efficacy of locally prepared intra-vaginal methylacetoxyprogesterone (MAP) sponges for estrus synchronization and conception rate in cyclic and acyclic Nili-Ravi buffaloes. In the first experiment, 20 buffaloes were divided into treated and control groups (n: 10 each) and again sub-grouped into cyclic (n: 4) and acyclic (n: 6) lots in each group, depending on their ovarian status. MAP sponges were placed in the vagina of buffaloes of treated groups for 16 days. After sponge removal, buffaloes were monitored for estrus. Serum progesterone concentrations were determined in synchronized animals for one estrous cycle using radioimmunoassay. Overall, synchronization rate in MAP-treated groups was significantly higher (P<0.05) as compared to controls (60 vs. 0%). However, it differed non-significantly between cyclic and acyclic buffaloes of treated groups (75 vs. 50%). At estrus, mean serum progesterone in synchronized animals was at basal level (0.26±0.08 and 0.32±0.27 ngml-1 in cyclic and acyclic treated groups, respectively). It attained peak levels of 3.00±1.80 to 3.45±0.44 ngml-1 on d-14, then dropped on d-18 and declined to basal values at the next estrus. In the second experiment, the effect of a MAP-based treatment was compared with an 11-days apart double injection prostaglandin (PGF2α) treatment for synchronization of estrus and conception rates. The estrus synchronization and conception rates obtained by PGF2α protocol were non-significantly higher than those of MAP-based protocol (90 vs. 70% and 44.44 vs. 42.86%). The synchronization and conception rates of cyclic buffaloes (80 & 50%, respectively) receiving MAP-based regimen were also non-significantly higher from acyclic ones (50 & 33%, respectively) receiving the same protocol. In conclusion, the treatment with locally prepared MAP sponges proved effective in synchronizing estrus and comparable with prostaglandin regimen in terms of conception rates in Nili-Ravi buffaloes.